Development of all-fiber pulsed lasers using bismuth- and thulium- doped fiber saturable absorber / Pei Zhang - Pei, Zhang (2022)
Due to the abundant advantages of low lasing threshold, simple configuration, high efficiency, long-time stability and low cost, all-fiber pulsed fiber lasers have attracted plentiful attentions in various applications such as materials processing, fast diagnosis, nonlinear optics, biomedicine, communication etc. Compared with other saturable absorber (SA), using the doped fiber saturable absorber (DFSA) is an effective and efficient method to realize all-fiber pulsed lasers. In this thesis, bismuth-doped fiber (BDF) and thulium-doped fiber (TDF) with different lengths are used to construct DFSAs. All DFSAs are characterized to ensure the linear and nonlinear absorption before being inserted into the typical ring cavity of fiber lasers. Q-switching, mode-locking and other operation modes are experimentally demonstrated in the erbium-doped fiber laser (EDFL) and neodymium-doped fiber laser (NDFL). The formation mechanism and performance characteristics of different pulses are systematically studied and analyzed in the all-fiber pulsed lasers with different configurations. Firstly, the 15cm and 30 cm Bismuth-DFSAs have been used to achieve all-fiber Q-switched EDFLs. The pulse width of Q-switching pulses by using 30 cm bismuth-DFSA is 1.18 μs, which is shorter than 3.66 μs by using 15 cm bismuth-DFSA. The 15 cm bismuth-DFSA is applied to successfully generate triple-wavelength vector dark solitons in self-starting mode-locking EDFL. The operating wavelengths are located at 1595 nm, 1598 nm, and 1602 nm simultaneously and the repetition rate is 1.89 MHz. Secondly, the 18 cm thulium-DFSA is used to generate Q-switching pulses in single and dual-wavelength Q-switched EDFL. The operating wavelengths of dual-wavelength operation are located at 1532.6 nm and 1557nm. By simply adjusting the polarization, the dual-wavelength operation can be switched into two single-wavelength operations at 1532 nm and 1558 nm, respectively. The single-wavelength all-fiber laser at 1532nm have better performance than that at 1558 nm, such as shorter pulse width, higher repetition rate and higher SNR. The 12 cm thulium-DFSA is used to generate ultrashort pulses in mode-locking EDFL at the wavelength of 1568.2 nm. The pulse width of mode-locking pulses is 2.27 ps with a repetition rate of 0.99 MHz and a SNR of 63 dB. Thirdly, Q-switching, Q-switched mode-locking and mode-locking operation modes are sequentially realized in a self-starting EDFL by using 12 cm thulium-DFSA. In addition, the 30 cm bismuth-DFSA is used to realize a dual-wavelength NDFL at 1080.8 nm and 1090.2 nm as a filter. A pure sinusoidal continuous wave is generated with the frequency of 9.1 MHz. Besides the sound stability of lasers, DFSAs have been proved to have higher damage threshold than other SAs, and furthermore possesses the ability of generating ultrashort pulses in an all-fiber laser for the first time.